2019
DOI: 10.21315/mjms2019.26.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Blood Safety among Blood Donors in Kelantan, Malaysia

Abstract: BackgroundUnsafe blood products may cause transfusion-transmissible infections. This study aimed to evaluate the knowledge and perceptions of blood donors regarding blood safety.MethodsThis was a cross-sectional study conducted in the Kelantan state of Malaysia. The questionnaire comprised 39 questions that covered areas such as donors’ social demographic information, knowledge of transfusion-transmitted diseases, blood screening and donor eligibility and perceptions towards blood safety. The knowledge score w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
0
3
0
5
Order By: Relevance
“…In line with other studies involving health science students, Musa and Shaaban (2019) observed low levels of awareness about donation requirements. Similarly, in a study conducted by Tan et al (2019), poor knowledge or awareness about blood donation was reported. From all the results stated above, there are still people with low awareness of blood donation.…”
Section: Awareness Towards Blood Donationmentioning
confidence: 89%
See 1 more Smart Citation
“…In line with other studies involving health science students, Musa and Shaaban (2019) observed low levels of awareness about donation requirements. Similarly, in a study conducted by Tan et al (2019), poor knowledge or awareness about blood donation was reported. From all the results stated above, there are still people with low awareness of blood donation.…”
Section: Awareness Towards Blood Donationmentioning
confidence: 89%
“…According to the findings of a study carried out by Salimah et al (2018), the respondents have a low level of knowledge about blood donation. Research findings by Tan et al (2019) also point to only 18.5% of the donors having adequate knowledge, while 81.5% had inadequate knowledge. The research conducted by Sham et al (2019) revealed that the desire to help others and establish good practice was ranked as the most important factor (98%) for blood donation.…”
Section: Introductionmentioning
confidence: 96%
“…Os jovens constituem público-alvo para doação de sangue pela tendência de serem saudáveis, dinâmicos e com muitos anos de vida pela frente 10,11 . Entretanto, captar e fidelizar doadores é um grande desafio para os serviços de hemoterapia 4, [16][17][18][19][20][21][22][23][24][25][26] . Este estudo analisou CAPs dos estudantes de medicina frente à escassez de sangue iniciada em março de 2020 e perpetuada a partir do mês de abril do mesmo ano, devido à instauração de um cenário pandêmico pela COVID-19 [27][28][29][30][31][32] , revelando os principais pontos a serem trabalhados e divulgados, com o intuito de ajudar no desenvolvimento das próximas campanhas de doação de sangue e entender as principais barreiras e incentivos, a fim de obter um maior número de doadores.…”
Section: Discussionunclassified
“…Embora os jovens estejam rodeados de informações rápidas e de fácil acesso veiculadas em mídias públicas, redes sociais e no ensino superior, durante a graduação, constatou-se na presente amostra, conhecimento inadequado 16,21,25 nas indagações significativas ao estudo.…”
Section: Discussionunclassified
“…Prevention of TTIs depends critically on understanding of the knowledge, attitude, and risk behavior of first-time blood donors. Blood donor screening questionnaires, which are crucial for determining health status and infection risk, may have limitations due to the fact that some donors may not completely disclose deferrable risk behavior as a result of the socially sensitive nature of questions [ 7 ]. By recognizing high-risk behavior, early intervention and counseling can be provided, to safeguard the blood supply [ 8 ].…”
Section: Introductionmentioning
confidence: 99%